(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
A sleeve gastrectomy is a life changing surgery which used for helping patients who are severing from obesity (BMI 40+ or BMI 35+ with other health problems) for losing weight and enhance their health weight loss help to less the risk for development medical conditions related to obesity as high blood pressure, D.M, arthritis, respiration problems), the sleeve gastrectomy operation makes stomach small to change the amount of meals, and it helps to losing weight. This study aims to assess nurses’ knowledge toward quantification sleeve gastrostomy in surgical unit and to identify the relationship between nurses’ knowledge about quantification sleeve gastrostomy and their sociodemographic data in surgical unit. A quantitative descriptive design is used in the present study to perform objectives. A purposive sampling method; 40 nurses distributed on hospitals in surgical units, the data collection used through constructed questions divided to demographic data and nurses’ knowledge, and data analyzed by descriptive analysis and an Inferential analysis. Nurses’ knowledge about sleeve gastrostomy was ranging between poor to moderate, and as general the total score of nurses’ knowledge was poor and no significant association between nurses’ knowledge and their demographic characteristics.